Symbol and Reality - Hamburg, Carl H. author. aut Link
172 p. 1 illus.
Keywords: Since prefaces, for the most part, are written after a book is done, yet face the reader before he gets to it, it is perhaps not surprising that we usually find ourselves addressed by a more chastened and qualifying author than we eventually encounter in the ensuing pages. It is, after all, not only some readers, but the writer of a book himself who reads what he has done and failed to do. If the above is the rule, I am no exception to it. The discerning reader need not be told that the following studies differ, not only in the approaches they make to their unifying subject-matter, but also in their precision and thus adequacy of presentation. In addition to the usual reasons for this rather common shortcoming, there is an another one in the case of the present book. In spite of its comparative brevity, the time-span between its inception and termination covers some twenty years. As a result, some (historical and epistemological) sections reflect my preoccupation with CASSI RER'S eady works during student days in Germany and France. When, some ten years later, CASSIRER in a letter expressed "great joy" and anticipation for a more closely supervised con tinuation of my efforts (which, because of his untimely death, never came to pass), he gave me all the encouragement needed to go to work on a critical exposition of his "symbolic form" con cept.